2014
DOI: 10.1093/nar/gku778
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of AUF1-mediated follistatin mRNA decay during glucose starvation protects cells from apoptosis

Abstract: Follistatin (FST) performs several vital functions in the cells, including protection from apoptosis during stress. The expression of FST is up-regulated in response to glucose deprivation by an unknown mechanism. We herein showed that the induction of FST by glucose deprivation was due to an increase in the half-life of its mRNA. We further identified an AU-rich element (ARE) in the 3′UTR of FST mRNA that mediated its decay. The expression of FST was elevated after knocking down AUF1 and reduced when AUF1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Cellular glucose levels also regulate AUF1 shuttling to the nucleus and AMPK is important for this effect (Gao et al ., 2014). Here, we found that AMPK is also important in mediating the effects of metformin on AUF1 redistribution to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular glucose levels also regulate AUF1 shuttling to the nucleus and AMPK is important for this effect (Gao et al ., 2014). Here, we found that AMPK is also important in mediating the effects of metformin on AUF1 redistribution to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical ARE sequence is distinguished by the presence of AUUUA pentamers, frequently in multiple and/or overlapping arrangements, within a U‐rich region that may range in size from 40 to 150 nucleotides . Besides AUF1, these sequences provide binding sites for a diverse array of factors collectively termed ‘ARE‐binding proteins.’ Depending on the specific factor recruited, protein binding may stabilize or destabilize the mRNA, or alternatively alter its translational potential …”
Section: The Auf1 Protein Familymentioning
confidence: 99%
“…FST is up-regulated during glucose deprivation and plays a protective role 13 14 . We hypothesized that FST is also a SiO 2 NP-responsive protein.…”
Section: Resultsmentioning
confidence: 99%
“…The TGF-β-like molecule-neutralizing effect of FST contributes to most of its functions 10 11 12 . Recent studies showed that FST also plays a protective role under cellular stresses including oxidative stress 13 14 15 . For example, activin induces endothelial cell oxidative stress and endothelial cell dysfunction, and these effects are mitigated by follistatin 15 .…”
mentioning
confidence: 99%